The AI Revolution in Multimorbidity Management: A Guide for Professionals and the Public - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Multimorbidity, the co-existence of two or more chronic conditions in a single individual, represents one of the most significant challenges in modern health...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Medical Ethics; Patient Care